A variant of the Cox algorithm for the imputation of non-response of qualitative data - Favre, Anne-Catherine; Matei, Alina; Tillé, Yves (My University, 2004)
The Coxalgorithm allows to round randomly and unbiasedly a table of real numbers without modifying the marginal totals. One possible use of this method is the random imputation of aqualitative variable in survey sampling. A modification of the Coxalgorithm is proposed in order to take into account a weighting system, which is commonly used in survey sampling. The use of this new method allows to construct a controlled imputation method that reduces the imputation variance.